Hubungan antara Kecerdasan Kinestetik dan Kepercayaan Diri Siswa dengan Hasil Belajar Tari Piring Pada Siswa Kelas VIII di SMP Regina Pacis Bogor - Ariandini; Triana, Dinny Devi; Suwandi, Tuteng (Program Studi Pendidikan Tari FBS UNJ, 2024)
This study aims to find out how big the relationship is between Kinesthetic Intelligence and Student Confidence with Dance Learning Outcomes. This study uses a quantitative research method with a correlational research design. The data collection technique used the Stratified Random Sampling technique with a total population of 215 students and a sample of 139 students. The results showed that: (1) There is a relationship between kinesthetic intelligence and learning outcomes of the Plate dance with the Pearson Correlation showing 0.149 and a determination coefficient of 82% (2) There is a relationship between self-confidence and learning outcomes of the Plate dance with the Pearson Correlation showing 0.497 and coefficient of determination of 81% (3) There is a significant relationship between kinesthetic intelligence and self-confidence of 0.002 <0.05 with a positive correlation and a coefficient of determination of 68% (4) There is a relationship between X1 and X2 with Y, the results of the study are simultaneously known coefficient of determination of 84%. Kinesthetic intelligence and student self-confidence influence each other and can contribute to the learning outcomes of plate dance in class VIII students at SMP Regina Pacis Bogor. Keywords: Kinesthetic Intelligence, Confidence, Learning Outcomes, Plate Dance.